2015
DOI: 10.1002/jbm.b.33562
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of singlet oxygen production from photosensitizer‐incorporated, medically relevant hydrogels

Abstract: Photodynamic therapy and photodynamic antimicrobial chemotherapy are widely used, but despite this, the relationships between fluence, wavelength of irradiation and singlet oxygen (1O2) production are poorly understood. To establish the relationships between these factors in medically relevant materials, the effect of fluence on 1O2 production from a tetrakis(4‐N‐methylpyridyl)porphyrin (TMPyP)‐incorporated 2‐hydroxyethyl methacrylate: methyl methacrylate: methacrylic acid (HEMA: MMA:MAA) copolymer, a total en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…45,77,78 The reduction in ADPA absorbance indicated the generation and reaction of 1 O 2 with ADPA to form an endoperoxide, which had no absorbance at 378 nm due to the breakdown of the anthryl chromophore. 79 As a negative control, we monitored the reduction of absorbance when ADPA was combined with RBloaded micelles in the dark and found that there was negligible production of 1 O 2 over at least 20 min (Figure S15). We then explored the influence of the concentration of micelles exposed to yellow light on the rate of 1 O 2 release in PBS.…”
Section: ■ Resultsmentioning
confidence: 99%
“…45,77,78 The reduction in ADPA absorbance indicated the generation and reaction of 1 O 2 with ADPA to form an endoperoxide, which had no absorbance at 378 nm due to the breakdown of the anthryl chromophore. 79 As a negative control, we monitored the reduction of absorbance when ADPA was combined with RBloaded micelles in the dark and found that there was negligible production of 1 O 2 over at least 20 min (Figure S15). We then explored the influence of the concentration of micelles exposed to yellow light on the rate of 1 O 2 release in PBS.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The optical property of DPBF was sensitively affected by 1 O 2 [ 27 ]. With DPBF as the 1 O 2 capture agent, the 1 O 2 generation efficiency of TPP in Gel can be calculated from the slopes of DPBF absorbance variation (410 nm) in the presence of photosensizers.…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, Craig et al reported an improved method tailored to the analysis of porphyrin-hydrogels using anthracene-9,10-dipropionic acid, which undergoes photobleaching at the 378 nm absorption band via endoperoxide formation. 189,190 For hydrogels, this is compounded by the need to measure singlet oxygen generation (with its short lifetime) in an aqueous environment and to account for the possibility of the sensor migrating into the matrix. Electron paramagnetic resonance, microwave spectroscopy and mass spectrometry can be considered as direct methods that can be used for singlet oxygen determination in hydrogels.…”
Section: Singlet Oxygen Determinationmentioning
confidence: 99%